2010
DOI: 10.1103/physrevb.81.161304
|View full text |Cite
|
Sign up to set email alerts
|

Probe and control of the reservoir density of states in single-electron devices

Abstract: We present a systematic study of the density of states ͑DOS͒ in electron accumulation layers near a Si-SiO 2 interface. In the experiments we have employed two conceptually different objects to probe DOS, namely, a phosphorus donor and a quantum dot, both operating in the single-electron tunneling regime. We demonstrate how the peaks in reservoir DOS can be moved in the transport window independently of the other device properties. This method introduces a fast and convenient way of identifying excited states … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…A drawback of the hydrogen-resist technique is that the electronic coupling to the contacted object cannot be tuned much once the device has been fabricated [7,8,10]. Moreover, the reduced dimensionality of the contacts and the random arrangement of dopants within the patterned regions lead to a peaked density of states (DOS), which can affect cryogenic transport measurements such as bias spectroscopy in the Coulomb-blockade (CB) regime [11][12][13]. It is thus important to understand how the geometry, separation and width of such degenerately doped contacts affect electrical transport.…”
Section: Introductionmentioning
confidence: 99%
“…A drawback of the hydrogen-resist technique is that the electronic coupling to the contacted object cannot be tuned much once the device has been fabricated [7,8,10]. Moreover, the reduced dimensionality of the contacts and the random arrangement of dopants within the patterned regions lead to a peaked density of states (DOS), which can affect cryogenic transport measurements such as bias spectroscopy in the Coulomb-blockade (CB) regime [11][12][13]. It is thus important to understand how the geometry, separation and width of such degenerately doped contacts affect electrical transport.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed study of this quasi-one-dimensional DOS in narrow MOS structures can be found in Ref. 17. The results in Fig.…”
mentioning
confidence: 95%
“…16 Very recently, an efficient technique to probe and control the reservoir density of states has been developed. 17 Here, we use this method to pinpoint the origin of the resonant tunneling features in our device. Figures 3͑a͒ and 3͑c͒ show bias spectroscopy data for the 0-1 transition of the dot at B ʈ = 4 T and 7 T. The shift of the charge transitions in gate space compared to Fig.…”
mentioning
confidence: 99%
“…In particular, the barrier gate voltage (V BG ) can be used to tune the donor electrochemical potentials into resonance with those of the source and drain reservoirs, inducing electron transport. The electron density in the source and drain reservoirs can be tuned in situ by the top gate voltage (V TG ), 18 while the lithographic width of the barrier gate influences the width, and therefore the transparency, of the tunnel barriers between donor and reservoirs. The excitation spectrum of the donor and its magnetic field dependence extracted from the transport measurements provide important information on electronic properties of donors in close proximity to gate electrodes and induced electron layers.…”
mentioning
confidence: 99%